The Influence of Principal Leadership Style and Teacher Work Motivation on Teacher Performance Through Job Satisfaction: A Study in Public Junior High Schools of Serang Regency - Atikah (Journal of Education and Teaching Learning, 2026)
Objective: This study aims to examine the effect of principal leadership style and teacher work motivation on teacher performance, with job satisfaction as a mediating variable, in public junior high schools in Serang Regency. Methodology: A quantitative approach with a cross-sectional survey design was employed. Data were collected via a 1-to-5 Likert scale questionnaire distributed to 122 teachers across six public junior high schools in Baros and Petir Sub-districts, selected using a proportionate stratified random sampling technique. The questionnaire was administered online through Google Forms and completed voluntarily by the participants. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software version 4.0, which included evaluations of both the measurement and structural models using a 5,000-iteration bootstrapping procedure. Results: Principal leadership style and teacher work motivation both had a significant positive effect on teacher job satisfaction, with path coefficients of 0.715 and 0.450 (), respectively. Job satisfaction was proven to be a significant mediator, showing indirect effects of 0.402 for leadership style and 0.254 for work motivation on teacher performance. Among the three predictors, job satisfaction exerted the largest direct effect on teacher performance, with a path coefficient of 0.563. The structural model accounted for 81.6% of the variance in job satisfaction and 90.2% of the variance in teacher performance. Conclusion: Teacher performance increases when principals lead adaptively, teacher work motivation is sustained, and the work environment fosters high job satisfaction. Job satisfaction serves as a vital bridge connecting leadership and motivation to daily teaching performance, highlighting the need to manage all three factors synchronously rather than in isolation. Limitations: Data were collected through self-reported measures at a single point in time, presenting potential common method bias. Additionally, discriminant validity tests indicated a high correlation between job satisfaction and teacher performance, suggesting that findings involving these two variables should be interpreted with caution. Finally, the geographic scope—limited to two sub-districts—restricts the generalizability of the findings to broader regions. Contribution: This study provides empirical evidence on the mediating role of job satisfaction in the relationship between leadership, motivation, and teacher performance in junior high schools. The findings offer practical insights for school principals, the Serang Regency Education Department, and educational researchers seeking to design targeted policies for school leadership development and teacher well-being programs.Objective: This study aims to examine the effect of principal leadership style and teacher work motivation on teacher performance, with job satisfaction as a mediating variable, in public junior high schools in Serang Regency. Methodology: A quantitative approach with a cross-sectional survey design was employed. Data were collected via a 1-to-5 Likert scale questionnaire distributed to 122 teachers across six public junior high schools in Baros and Petir Sub-districts, selected using a proportionate stratified random sampling technique. The questionnaire was administered online through Google Forms and completed voluntarily by the participants. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software version 4.0, which included evaluations of both the measurement and structural models using a 5,000-iteration bootstrapping procedure. Results: Principal leadership style and teacher work motivation both had a significant positive effect on teacher job satisfaction, with path coefficients of 0.715 and 0.450 (), respectively. Job satisfaction was proven to be a significant mediator, showing indirect effects of 0.402 for leadership style and 0.254 for work motivation on teacher performance. Among the three predictors, job satisfaction exerted the largest direct effect on teacher performance, with a path coefficient of 0.563. The structural model accounted for 81.6% of the variance in job satisfaction and 90.2% of the variance in teacher performance. Conclusion: Teacher performance increases when principals lead adaptively, teacher work motivation is sustained, and the work environment fosters high job satisfaction. Job satisfaction serves as a vital bridge connecting leadership and motivation to daily teaching performance, highlighting the need to manage all three factors synchronously rather than in isolation. Limitations: Data were collected through self-reported measures at a single point in time, presenting potential common method bias. Additionally, discriminant validity tests indicated a high correlation between job satisfaction and teacher performance, suggesting that findings involving these two variables should be interpreted with caution. Finally, the geographic scope—limited to two sub-districts—restricts the generalizability of the findings to broader regions. Contribution: This study provides empirical evidence on the mediating role of job satisfaction in the relationship between leadership, motivation, and teacher performance in junior high schools. The findings offer practical insights for school principals, the Serang Regency Education Department, and educational researchers seeking to design targeted policies for school leadership development and teacher well-being programs.